Chemotherapy Remote Care Monitoring Program: Integration of SMS Text Patient-Reported Outcomes in the Electronic Health Record and Pharmacist Intervention for Chemotherapy-Induced Nausea and Vomiting. Issue 9 (September 2021) - Hough, Shannon; McDevitt, Rachel; Nachar, Victoria R.; Kraft, Shawna; Brown, Anna; Christen, Catherine; Frame, David; Smerage, Jeffrey B.
Abstract : PURPOSE: Chemotherapy-induced nausea and vomiting (CINV) is a common cause of unplanned healthcare utilization. The University of Michigan Rogel Cancer Center initiated the chemotherapy remote care monitoring program (CRCMP) to proactively identify patients experiencing CINV and intervene before the need for urgent evaluation. METHODS: High-risk patients for CINV are identified by neurokinin-1 (NK-1) antagonist administration, enrolled in the CRCMP, and received a daily text message survey for 7 days after chemotherapy administration to report symptoms. Responses above a set threshold trigger a message to the team pharmacist for intervention. The primary outcome of 14-day unplanned healthcare use was evaluated before and after CRCMP implementation. RESULTS: In 8 months, 652 patients received an NK-1 antagonist (2, 244 cycles) and 387 patients were enrolled in the CRCMP (59%). Text message response rate was 94%. Clinical pharmacists provided 248 interventions in 121 patient episodes meeting threshold criteria. Fourteen-day unplanned healthcare use was decreased in the CRCMP-enrolled NK-1 episodes (6.68% v 4.53%, P = .02). Admissions were numerically lower for those enrolling in CRCMP when only admissions for nausea were considered (0.63% v 0.35%, P = .33). CONCLUSION: The CRCMP allowed for real-time management of patient-reported CINV symptom burden based on patient-reported outcomes (PROs) and an electronic medical record-integrated SMS text questionnaire. Clinical pharmacists were key team members to manage patient symptoms. Enrollment in CRCMP significantly reduced overall unplanned healthcare utilization. Although these changes were numerically small, any reduction in unnecessary care utilizing PROs can contribute to high-value care for patients with cancer.